Examinations timetable management system / Namirah Hamdan - Hamdan, Namirah (2020)
All university produce the examination timetables as one of the academic activities that must be implemented. The examination timetable is produced by each institution which is different from the type of institution involved and also the influence of constraints. The purpose of preparing the examinations timetable is to ensure that each examination runs smoothly and every student can sit for examination without any problems. There are difficulty in allocating which examinations to be placed in which rooms due to the limited number of rooms and also difficulty in searching for which room for examination seat. Thus, a system that is able to allocate the examinations to available room and view complete examinations timetable should be developed. This project aimed to develop system that generate examinations timetable that allocate examinations to classroom and view the complete examinations timetable. The scopes for this system is academic registrar and FSKM students. Moreover, the main focus of this system is to satisfy some sets of constraints such as hard and soft constraint. There are two types of testing that have be done which are functionality testing and usability testing. This study have proved that this system gives positive feedback in generating an examinations timetable and providing students with the examinations timetable that they can easily find in which room they need to attend to sit for examinations.